The Influence of Financial Literacy and Digital Awareness on the Intensity of QRIS Transactions among Members of the Pandansari Youth Organization in Bantul, Special Region of Yogyakarta, in the Era of a Cashless Society - Nenden Susilowati; Irma Senia Wafiroh; Naura Kholda Khoirunisa; Berliani Monika Satu; Nadila Mutiara Aisyah (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
This study aims to analyze the influence of financial literacy and digital awareness on the intensity of transactions using QRIS at Karang Taruna Pandansari Bantul, Yogyakarta Special Region, in the era of a cashless society. The background of this study was conducted because it observed the phenomenon of the use of non-cash transactions, such as QRIS, which are able to provide convenience, efficiency, and security in daily payment activities. This study used a quantitative method through questionnaire distribution. Then the research instrument was tested for validity and reliability to ensure data accuracy. Data analysis was carried out using the multiple linear regression method to test the influence of independent variables, namely financial literacy and digital awareness, both simultaneously on the intensity of QRIS transactions. The results of this study stated that a better understanding of financial management has a positive and significant impact on the frequency of transactions using QRIS. The more people know about financial management, the more likely they are to use QRIS as a practical, effective, and secure payment tool. It is proven that understanding and skills in digital technology can increase the interest and intensity of people who transact through QRIS. At the same time, financial literacy and digital awareness also have a positive and significant impact on transaction intensity. These two components can work together to encourage people, especially the younger generation, to become more adaptive to advances in contemporary financial technology. Keywords: Digital Awareness, Financial Literacy, Transaction Intensity, QRIS.